A PCA-BASED METHOD FOR REMANUFACTURING PROCESS OPTIMIZATION FROM SUSTAINABILITY ASPECTS - Shi, Junli; Xu, Huanhuan; Shu, Fangli; Ren, Mengmeng; Lu, Zhongchi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
The optimization of the remanufacturing process is an important issue in remanufacturing activities because it affects the performance and quality level of remanufactured products to a great extent. However, the implementation of the remanufacturing process is affected by many factors, such as technical, environmental, economic, and social factors, to different degrees. To implement remanufacturing effectively, a remanufacturing process optimization method is developed on the basis of principal component analysis (PCA) theory from the aspect of sustainability. In this method, the system boundary is first defined, and then the remanufacturing process is designed to be associated with four main sustainability criteria: technical process, economic cost, environmental effect, and social influence. Each criterion includes several indicators, which total up to sixteen. Afterward, the sixteen sustainability indicators are reduced to three main indicators via PCA dimension reduction method. Finally, the remanufacturing process is optimized by the construction comprehensive evaluation function of the three main indicators. To verify the effectiveness of the method, diesel engine remanufacturing is taken as the case.